Rheumatoid leptomeningitis presenting with an acute neuropsychiatric disorder. Issue 1 (10th August 2018) - Lubomski, Michal; Sy, Joanne; Buckland, Michael; Lee, Andie S; Richards, Bethan; Thompson, Elizabeth; Fulham, Michael; Breen, Nora; Morris, Kirsty; Halmagyi, G Michael
Abstract : Leptomeningitis is a rare central nervous system manifestation of rheumatoid arthritis, generally in patients with established chronic rheumatoid disease. We report a 41-year-old man without previous rheumatoid arthritis or psychiatric disorder who presented with an acute neuropsychiatric disturbance and polyarthralgia. His MR scan of brain showed asymmetric bifrontal leptomeningitis, confirmed on (18F)-fluoro-D-glucose-positron emission tomography. Other investigations showed highly positive serum and cerebrospinal fluid anti-cyclic citrullinated peptide. A leptomeningeal biopsy showed necrotising leptomeningeal inflammation with ill-defined granulomas and lymphoplasmacytic infiltrate without organisms. Prolonged high-dose corticosteroids and then rituximab resulted in recovery. Chronic leptomeningitis can present with an acute neuropsychiatric disorder. We highlight that early rheumatoid disease can, rarely, cause a chronic leptomeningitis, reversible with immunotherapy.